Evaluating English Language Instruction Using the Smart Unilak System: A Student-Based Longitudinal Analysis (2018-2024) - Indah Muzdalifah; Dafwen Toresa; Fana Wiza; Vivi Indriyani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Evaluation and assessment play vital roles in language acquisition and overall teaching effectiveness. Despite their importance, research on English language instruction evaluation in Indonesian universities remains scarce. Many lecturers resist classroom evaluation, often viewing teaching as merely delivering content without ongoing reflection or feedback mechanisms. This study uses a quantitative descriptive approach to analyze archival student feedback data collected through an e-learning platform’s questionnaire feature. The research focuses on one lecturer teaching the MKDU English course since 2016, involving 57 classes across 9 study programs from 4 faculties: Engineering, Agriculture, Business, and Law. The questionnaire, consisting of 26 items, served as a reliable instrument for evaluating classroom instruction. Over six years, the lecturer consistently received scores ranging from 4 to 5 on a Likert scale, translating to "very good." The average questionnaire results exceeded 80%, placing the lecturer in the “excellent” category based on the eligibility percentage formula (76%–100%). These findings highlight the effectiveness of structured student feedback in evaluating language instruction. The lecturer’s sustained high scores suggest strong teaching performance and effective engagement across multiple disciplines. This study confirms that student feedback via e-learning platforms can serve as a valid and reliable tool for evaluating English language instruction. The examined lecturer demonstrates consistently excellent performance over six years, reinforcing the value of systematic assessment in language education.